Calcitonin negative medullary thyroid cancer in ectopic thyroid tissue: a rare diagnosis in an unusual location. Issue 8 (18th August 2020) - Montgomery, Gareth; Collins, Laurence; Coghlin, Caroline; Ullah, Ramzan
Abstract : Medullary thyroid cancer is an aggressive form of thyroid cancer arising from parafollicular C cells. Calcitonin (CT) is a specific and sensitive biochemical marker which typically aids primary diagnosis and disease surveillance following treatment. There are rare cases of calcitonin negative medullary thyroid cancer (CNMTC) documented in the literature; however, to our knowledge, this case is the first report of CNMTC arising in ectopic thyroid tissue. We report a case of a 45-year-old man who attended his primary care physician with painless anterior neck swelling. In the absence of CT secreting disease, we have demonstrated the investigative process and the importance of immunohistochemical analysis to achieve a diagnosis. We also consider the challenges of monitoring disease recurrence in the absence of reliable biochemical markers.